Folk medicinal plants of Trabzon (Turkey) - (:unkn) unknown (My University, 1996)
Folk medicinal plants of Trabzon (Turkey) were investigated between July 1992 and June 1993. It has been found that 67 species recorded from 33 different places are being used as folk medicine, among them 42 species are wild and 25 species are cultivated plants. The folk medicinal plants are mostly used for the treatment of bronchitis, rheumatism, hemorrhoids, diabetes, gastrointestinal disorders, wounds, eczema and as analgesic.
Keywords: folk medicine; medicinal plants; Turkey